Beyond Crisis Care in Brain Injury Rehabilitation in Australia - Heidi Muenchberger PhD; Elizabeth Kendall PhD; Catherine Collings BSocWk (SAGE Publishing, 2011)
Objective: The aim of this commentary was to bring together the various significant issues associated with delivering brain injury rehabilitation in Australia. Through observational critique, the authors aimed to identify gaps in practice and opportunities for change. Approach: In light of Australia's national health reform process, it is necessary to consider rehabilitation practices and models for brain injury service delivery. There are lessons to be learned within the Australian system, but also opportunities to apply international reform. Conclusion: For those within the service delivery system, brain injury rehabilitation can often appear to be a crisis-driven response. Gaps in service provision persist, leaving individuals who have reduced cognitive and emotional capacity to self-navigate an unpredictable health system at a time in their lives when they are least prepared to do so. Deficiencies in the delivery of timely and appropriate psychosocial or behavioral rehabilitation services undoubtedly contribute to the current pressures on the health system created by increased length of stay in neurological and slow-to-recover rehabilitation units, repeat presentations to primary care, and frequent use of community mental health services. Implication: The experiences of people with acquired brain injury highlights the need for early and targeted interventions that can deal with emerging complexities and support needs, interorganizational approaches, and new accommodation options with a matched service philosophy. Rather than count on good fortune, individual outcomes, and the future of brain injury, rehabilitation ought to depend on deliberate and systemic design.